1991
DOI: 10.1113/jphysiol.1991.sp018669
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of the response of cat spindle Ia afferents to sinusoidal stretch on the velocity of concomitant movement.

Abstract: SUMMARY1. The responses of de-efferented soleus muscle spindle primary afferents to 1 Hz sinusoidal stretches, which were superimposed on triangular background movements of intermediate amplitude (1P2 mm, half peak-to-peak) and widely varying speed, were recorded in anaesthetized cats.2. Compared with control responses to the same sinusoids applied at fixed mean muscle length, the sensitivity to small (50 and 100 ,um, half peak-to-peak), but not to large (1000 jtm), sinusoidal movements was dramatically reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…It may be questioned whether the responses to discontinuities found in the present study were dependent on the small-range high sensitivity as studied in the cat. The average step size of the 8-10 Hz discontinuities in the present study would be of the order of 0-13 mm in terms of tendon excursion (Edin & Vallbo, 1990a) (Baumann & Hulliger, 1991). Hence it is far from clear that the responses to the discontinuities of the present study are dependent on the high sensitivity range of the muscle spindles.…”
Section: Significance Of Conduction Timementioning
confidence: 52%
“…It may be questioned whether the responses to discontinuities found in the present study were dependent on the small-range high sensitivity as studied in the cat. The average step size of the 8-10 Hz discontinuities in the present study would be of the order of 0-13 mm in terms of tendon excursion (Edin & Vallbo, 1990a) (Baumann & Hulliger, 1991). Hence it is far from clear that the responses to the discontinuities of the present study are dependent on the high sensitivity range of the muscle spindles.…”
Section: Significance Of Conduction Timementioning
confidence: 52%
“…The peripheral effects of movement speed and corresponding afferent state, such as muscle spindle discharge regulated by the fusimotor system (Prochazka 1989), are also unlikely to account for the observed reflex modulation. This is because 1) we observed reflex modulation in the temporal set but not in the spatial set regardless of the identical changes in movement speeds in both sets, and 2) several studies have shown that as the speed of voluntary contraction increases, muscle spindle discharge rather decreases (Baumann and Hulliger 1991;Burke et al 1978). Second, the unchanged reflex amplitudes against the SPD (Fig.…”
Section: Temporal Setting Of Anticipatory Reflex Amplitudementioning
confidence: 60%
“…For example, Baumann and Hulliger (1991) report data indicating that the phenomenon of gain-compression is greatly reduced for movements which fail to satisfy highly restrictive length-and velocity-related criteria. On the basis of current evidence, therefore, we conclude that while such nonlinearities could, conceivably, alter the correlations we report it is unlikely that they will lead to significant reductions in the magnitudes of the observed correlations.…”
Section: Scaling Of Spindle Discharge Ratesmentioning
confidence: 96%